(untitled) (Research, Society and Development, 2020)
The study aims to analyze the national and international scientific biography about the workloads present in nursing care for elderly. A search was executed in July 2019, in five databases, establishing the criteria of inclusion and exclusion, in the final four studies were selected. The results highlighted aging as a natural process, showing that care for the elderly has particularities and being necessary to monitor the exposure of nursing workers to workloads for subsidize better working conditions and interventions in health institutions. Concludes that if they improve working conditions the workers have less exposure to workloads and it will possibly increase the quality of care, affecting the life of the elderly person and his family.